Probiotics of the gender Bacillus in diets for Nil tilapia post-larves (Oreochromis niloticus) (Research, Society and Development, 2021)
In order to evaluate different levels of probiotic in diets for Nile tilapia post-larvae, 1,680 Nile tilapia post-larvae (0.05 ± 0.01g) were distributed in 24 110 L aquariums, in a completely randomized design with six treatments and four replications, considering as an experimental unit an aquarium with 70 fry. During the experiment, water quality parameters were monitored daily using a portable multiparameter probe and the water temperature (26.9 ± 0.5 ° C), dissolved oxygen (4.0 ± 0.7mg / L), electrical conductivity were evaluated. (170.1 ± 46.6 μS / cm) and pH (7.2 ± 0.5). A basal diet (control - 0.00) was formulated and levels of inclusion of probiotic of the genus Bacillus 4.0x 1012 CFU (0.02; 0.04; 0.06; 0.08; 0.10 g / 100g) were performed) of feed. At the end, the parameters of zootechnical performance and centesimal composition of the carcass were evaluated, where no differences were observed (P